Railway Detection Of Axle Detection Patterns Using The KNN Method - Winjaya, Fathurrozi; Feryando, Dara Aulia; Al Ghifari, Sultan Rasya Nair; Fajri, Saian Nur (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The track circuit is a device used to determine whether a vehicle is on the track. This device is installed on the track and needs to be monitored to ensure it functions properly. All objects detected in practice are considered railway vehicles, even though the detected objects may not be railway vehicles. Accurate and reliable detection technology is crucial for preventing accidents and keeping train traffic safe. This detection system uses metal sensors to identify objects as railway or non-railway assets. This is done based on two variables: the frequency of the object's metal and the object's speed. The test results show that this tool can classify objects according to their class. The class with no objects has an accuracy level of 100%, while the class of non-railway has an accuracy level of 86.67%. The railway class trials using the inspection train axle show an accuracy level of 93.33%.